FORMULATION OF HERBAL NASAL FORMULATION USING EXTRACTS OF ADINA CORDIFOLIA LEAVES AND SIDA SPINOSA LEAVES (International Journal of Food and Nutritional Sciences, 2022)
Nasal formulations represent a vital avenue for drug delivery, offering the potential for targeted and efficient delivery of therapeutic compounds. This study explores the development and formulation of a novel herbal nasal formulation utilizing extracts derived from Adina cordifolia leaves and Sida spinosa leaves, known for their remarkable medicinal properties. The objective of this research is to harness the therapeutic potential of these herbal extracts for various nasal applications, such as alleviating nasal congestion, managing allergic rhinitis, or treating sinusitis. The resulting herbal nasal formulation is subjected to rigorous quality control measures, including stability testing and microbiological evaluation, to ensure safety, efficacy, and compliance with regulatory standards. This research aims to contribute to the growing body of knowledge on herbal-based nasal formulations and their potential benefits in enhancing drug delivery and therapeutic outcomes. As the study bridges traditional herbal wisdom with modern pharmaceutical science, it underscores the significance of nature-derived therapies in addressing common nasal ailments. The findings from this investigation have the potential to pave the way for innovative herbal nasal products, offering a safe and natural approach to nasal health and wellness. Further clinical trials and evaluations may be warranted to validate the efficacy and safety of this herbal nasal formulation for specific nasal conditions.